Economics is whatever the comparative advantage of economists is: a comment on Leeson (2020). Issue 4 (6th August 2020) - Murphy, Ryan H.
Abstract: Leeson (2020) objects to the conflation of economics with applied econometrics, and argues that economics instead should be thought of as the implications of the assumption that individuals maximize, i.e. rational choice theory. But, narrowly defining economics in terms of method demands that we ignore alternative theoretical frameworks which potentially hold explanatory power about topics thought of as economics, all for the sake of a definition. I suggest that applying rational choice theory and applying econometrics became the comparative advantage for economists relative to other social scientists by accidents of history. These comparative advantages largely persist. It is reasonable to call applications of both rational choice theory and econometrics to topics outside conventional economic topics 'economics' simply because these applications remain the comparative advantage of economists.